Greenland, hanging glacier in Dicksons Fjord, Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig. 195 - A small hanging glacier in Dickson Fiord that reaches sea level. Aug. 6, 1931. (Caption from Boyd, L. A. (1935). The Fiord Region of East Greenland (pp.133). New York: American Geographical Society.) A small hanging glacier in Dickson Fiord that reaches sea level. Aug. 6, 1931. From Fiord Region of East Greenland, Fig. 195. Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society